Variational Method to the Impulsive Equation with Neumann Boundary Conditions. (11th October 2009) - Sun, Juntao; Chen, Haibo
Abstract : We study the existence and multiplicity of classical solutions for second-order impulsive Sturm-Liouville equation with Neumann boundary conditions. By using the variational method and critical point theory, we give some new criteria to guarantee that the impulsive problem has at least one solution, two solutions, and infinitely many solutions under some different conditions, respectively. Some examples are also given in this paper to illustrate the main results.